Can the Introduction of a Minimum Wage in FYR Macedonia Decrease the Gender Wage Gap? - Angel-Urdinola, Diego F. (2012)
This paper relies on a simple framework to understand the gender wage gap in Macedonia, and simulates how the gender wage gap would behave after the introduction of a minimum wage. First, it presents a new - albeit simple - decomposition of the wage gap into three factors: (i) a wage level factor, which measures the extent to which the gender gap is driven by differences in wage levels among low-skilled workers of opposite sex; (ii) a skills endowment factor, which quantifies the extent to which the gender wage gap is driven by the difference in the share of high-skilled workers by gender; and (iii) returns to education, which measures the extent to which the gender gap is driven by differences by gender in returns to education. Second, the paper presents simple set of simulations that indicate that the introduction of a minimum wage in Macedonia could contribute to decrease the gender wage gap by up to 23 percent. Nevertheless, in order to significantly improve the wage gap, a rather high minimum wage may be required, which may contribute to reductions in employment.